Genetic and morphological variation in taxonomically critical populations of Quercus petraea s.l. in Southern Europe - Romeo Di Pietro; Elisa Proietti; Piera Di Marzio; Amara Noor Hussain; Katharina Birgit Budde; Kryštof Chytrý; Leonardo Filesi; Oliver Gailing; Lorenzo Gianguzzi; Duilio Iamonico; Nevena Kuzmanović; Dmitar Lakušić; et al. (European Journal of Forest Research, 2026)
This study investigated the genetic and morphological variability of critical populations of Quercus petraea s.l. in southern Europe considering taxonomic and biogeographical issues. Ten EST-SSR markers were applied on sixteen populations of Q. petraea s.l., including Q. petraea subsp. petraea , Q. petraea subsp. austrotyrrhenica , Q. dalechampii auct non Ten, and Q. banatus , to assess genetic variation within and among populations using specific indices. Genetic structure was analysed using Bayesian clustering. Eight populations of potentially interfertile white oaks such as Q. pubescens (5) and Q. robur (3) were included in the overall dataset (24 populations) for comparison. Multivariate analysis procedures were applied to analyse genetic relationships among populations. The morphological variability of oak individuals was assessed only on the Q. petraea s.l. populations based on traits observed in leaves, twigs, and acorns. The patterns of covariation between morphological traits, taxonomic identity, and the geographical distribution of sessile oak populations were also investigated. The analysis on the overall dataset revealed four main genetic clusters for Q. petraea s.l.: one of possible ancestral origin, one occurring mainly in the Balkans, one spread across southern Italy, and one distributed primarly in western and central Europe. From a morphometric perspective, only a few leaf morphological traits exhibited variation trends correlated with the genetic structure pattern. Considerable overlap was found among populations within the Q. petraea collective group from both the genetic and morphological side. The variability observed was insufficient to distinguish species other than Q. petraea (Matt.) Liebl. (i.e. Q. dalechampii auct. non Ten., Q. banatus Kučera). However, all Q. petraea s.l. populations were found to be clearly distinguishable from the Q. robur subsp. robur and Q. pubescens subsp. pubescens populations included in the dataset as outgroups.

Modeling total ozone column using principal component analysis and artificial neural networks over Iraq (2013–2023) - Nagham T. Ibraheem; Jasim M. Rajab; Berivan Hadi Mahdi; Hwee San Lim; Ali M. Al-Salihi; Zahraa N. Al-Montaser; Hazim H. Hussain (Theoretical and Applied Climatology, 2026)

Higher endogenous labile organic carbon decreases the temperature sensitivity of soil organic matter decomposition in two subtropical forests - Di Ma; Yu Sun; Min Liu; Huajun Fang; Xingliang Xu (Applied Soil Ecology, 2025)

PoreSkel: Skeletonization of grayscale micro-CT images of porous media using deep learning techniques - Mehdi Mahdaviara; Mohammad Sharifi; Amir Raoof (Advances in Water Resources, 2023)

Pre- and post-drought conditions drive resilience of Pinus halepensis across its distribution range - Léa Veuillen; Bernard Prévosto; Raquel Alfaro-Sánchez; Vincent Badeau; Giovanna Battipaglia; Santiago Beguería; Felipe Bravo; Thomas Boivin; J. Julio Camarero; Katarina Čufar; Hendrik Davi; Martin De Luis; et al. (Agricultural and Forest Meteorology, 2023)

PoreSeg: An unsupervised and interactive-based framework for automatic segmentation of X-ray tomography of porous materials - Mehdi Mahdaviara; Mohammad Sharifi; Yousef Rafiei (Advances in Water Resources, 2023)

How interfacial dynamics controls drainage pore-invasion patterns in porous media - Mahdi Mansouri-Boroujeni; Cyprien Soulaine; Mohamed Azaroual; Sophie Roman (Advances in Water Resources, 2023)